Ketegangan Antara Individualitas Dan Sosialitas (Memahami Logika Pedagang Mojokuto) - Nugroho, Ganjar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2000)
raders, surely, are engaging economic activity based on the principle of pursuing their own self interest. The notion of self interest, however, is socially constructed. Observation at Mojokuto market-place shows that people sense of self interest do not necessarily egoistic. It is in their own interest to maximize the benefit of not being egoistic.